COUNTERVAILING 'MISSIONARY' FORCES: EMPIRE AND CHURCH IN ACTS - Punt, J. (Scriptura, 2010)
Scholarly consensus has long held that Acts was intended as some sort of Christian apology to the ruling authorities, serving to allay the fears of the imperial forces and their collaborators that the followers of Jesus posed no political threat. This scholarly edifice has been eroded somewhat, among others by the position that the source and direction of the apology were the reverse of the consensus position - a promotion of the imperial regime among followers of Jesus. Given these and other understandings of the imperial setting portrayed in Acts, the relationship between Acts and Empire clearly remains an unfinished and important discussion. Such interpretative positions regarding the relationship between Acts and Empire are briefly reviewed amidst first-century conceptions and positions of power, before highlighting a number of instances in Acts where this relationship comes to a head, suggesting also four possible avenues for further investigation.